Modern Money Theory on fiscal and monetary policies: Empirics, theory and policymaking - Éric Tymoigne (Levy Economics Institute of Bard College, 2024)
Drumetz and Pfister (2021) make several claims about the inadequacy and fallacies of Modern Money Theory (MMT) and conclude that MMT is nothing more than a political manifesto; there are no theoretical and empirical foundations behind it. This paper addresses this last point by focusing on the fiscal and monetary policy aspects of their criticisms. Contrary to what they claim, MMT is backed by a large body of empirical evidence, a rich institutional analysis, and a well-developed theoretical framework (including mathematical models). MMT provides a detailed analysis of the coordination between the fiscal and monetary branches of government, emphasizes that fiscal deficits are a stylized fact, and uses theoretical tools grounded in institutional realities to explain this stylized fact. In line with a large body of work, MMT concludes that fiscal policy, the provision of an elastic currency, and financial regulations have contributed to economic stability and growth; however government involvement can be improved by changing the policymaking praxis. MMT also concludes that fine-tuning of the economy via monetary policy is not effective and does not attribute the "great moderation" to better monetary management.
Keywords: E12; E58; E61; H62; H63; 330; Modern Money Theory; Monetary Policy; Fiscal Policy; Policy Coordination; Public Debt Sustainability